A cohort profile of the Graham Roberts study cohort - Russell, Beth; Leech, Poppy; Wylie, Harriet; Moss, Charlotte Louise; Haire, Anna; Enting, Deborah; Amery, Suzanne; Chatterton, Kathryn; Khan, Muhammad Shamim; Thurairaja, Ramesh; Nair, Rajesh; Malde, Sachin; et al. (Frontiers in Oncology, 2024)
Purpose The Graham Roberts Study was initiated in 2018 and is the first Trials Within Cohorts (TwiCs) study for bladder cancer. Its purpose is to provide an infrastructure for answering a breadth of research questions, including clinical, mechanistic, and supportive care centred questions for bladder cancer patients. Participants All consented patients are those aged 18 or older, able to provide signed informed consent and have a diagnosis of new or recurrent bladder cancer. All patients are required to have completed a series of baseline questionnaires. The questionnaires are then sent out every 12 months and include information on demographics and medical history as well as questionnaires to collect information on quality of life, fatigue, depression, overall health, physical activity, and dietary habits. Clinical information such as tumour stage, grade and treatment has also been extracted for each patient. Findings to date To date, a total of 125 bladder cancer patients have been consented onto the study with 106 filling in the baseline questionnaire. The cohort is made up of 75% newly diagnosed bladder cancer patients and 66% non-muscle invasive bladder cancer cases. At present, there is 1-year follow-up information for 70 patients, 2-year follow-up for 57 patients, 3-year follow-up for 47 patients and 4-year follow-up for 19 patients. Future plans We plan to continue recruiting further patients into the cohort study. Using the data collected within the study, we hope to carry out independent research studies with a focus on quality of life. We are also committed to utilising the Roberts Study Cohort to set up and commence an intervention. The future studies and trials carried out using the Roberts Cohort have the potential to identify and develop interventions that could improve the prevention, diagnosis, and treatment of bladder cancer.